Micro Rain Radar data collected at Davis, 2018-2019 - ALEXANDER, SIMON (hasPrincipalInvestigator); ALEXANDER, SIMON (processor); Australian Antarctic Data Centre (publisher)
This dataset comprises Micro Rain Radar data collected adjacent to the Bureau of Meteorology building at Davis Station, Antarctica between November 2018 and November 2019. The original Doppler spectra are also saved in these files. Parameters within the file include: Za – Attenuated Reflectivity (dbZ) Z – Reflectivity (dbZ) Ze - Equivalent Reflectivity (dbZ) Zea - Attenuated Equivalent Reflectivity (dbZ) RR – Rain Rate (mm/hr) LWC – Liquid Water Content (g/m^3) W – Fall Velocity (m/s) Dataset resolution: 35m x 10 s Height coverage: 30m – 4475m above instrument level.